Conservative surgical treatment of medication related osteonecrosis of the jaw (MRONJ) lesions in patients affected by osteoporosis exposed to oral bisphosphonates: 24 months follow-up. Issue 7 (July 2018) - Nisi, Marco; Karapetsa, Dimitra; Gennai, Stefano; Ramaglia, Luca; Graziani, Filippo; Gabriele, Mario
Abstract: The purpose of the study was to evaluate the efficacy of conservative surgical treatment of medication related osteonecrosis of the jaw (MRONJ) in patients affected by osteoporosis and exposed to oral bisphosphonates (BPs). Subjects diagnosed with MRONJ and osteoporosis under oral BPs that had undergone conservative surgery and had at least 24 months follow-up were included. All patients received medical-antibiotic therapy and then underwent conservative surgical treatment consisting of sequestrectomy, soft tissue debridement and bone curettage with limited or no extension. A total of 53 patients, mean age of 71.9 ± 10.2 years (range 41–87), were enrolled. Two years after conservative surgical therapy 45 patients (91.8%) showed complete healing. The presence of rheumatoid arthritis (p = 0.003) and a more severe initial MRONJ stage (p = 0.023) were associated with a negative surgical outcome while the presence of bone sequestrum was strongly associated with a positive outcome (p = 0.036). Conservative surgical treatment of MRONJ lesions in patients affected by osteoporosis and receiving only oral BPs may represent a valid therapeutic approach determining a high number of complete healing cases. Conservative surgery should be encouraged at early MRONJ stages and after medical therapy failure.